Innovative practices for teaching sign language interpreters - Roy, Cynthia B., 1950- (Gallaudet University Press, 2000)
"The concept of interpreters as passive conduits who translate text has been replaced, according to Roy's penetrating new work. Researchers now understand interpreting as an active process between two languages and cultures, and thus, social interaction, sociolinguistics, and discourse analysis are more appropriate theoretical frameworks. This perspective explores the social order of real-life, interpreter-mediated conversations in which interpreters process information at several levels and make intentional, informed choices from a range of possibilities. Innovative Practices for Teaching Sign Language Interpreters acts upon these new insights by presenting six dynamic teaching practices to help interpreters achieve the highest level of skill."--Jacket.